The Southern Annular Mode in 6th Coupled Model Intercomparison Project Models - Morgenstern, O. (Journal of geophysical research. Atmospheres, 2021)
I analyze trends in the Southern Annular Mode (SAM) in CMIP6 simulations. For the period 1957–2014, simulated linear trends are generally consistent with two observational references but seasonally in disagreement with two other representations of the SAM. Using a regression analysis applied to model simulations with interactive ozone chemistry, a strengthening of the SAM in summer is attributed nearly completely to ozone depletion because a further strengthening influence due to long‐lived greenhouse gases is almost fully counterbalanced by a weakening influence due to stratospheric ozone increases associated with these greenhouse gas increases. Ignoring such ozone feedbacks would yield comparable contributions from these two influences, an incorrect result. In winter, trends are smaller but an influence of greenhouse gas‐mediated ozone feedbacks is also identified. The regression analysis furthermore yields significant differences in the attribution of SAM changes to the two influences between models with and without interactive ozone chemistry, with ozone depletion and GHG increases playing seasonally a stronger and weaker, respectively, role in the chemistry models versus the no‐chemistry ones. Plain Language Summary The Southern Annular Mode consists of a see‐saw of atmospheric mass between southern middle and high latitudes. It is subject to human influences due to ozone loss (esp. the ozone hole) and global warming. Here I show, using a regression analysis performed on simulations recently produced by present‐generation climate models, that the ozone loss influence is dominant in summer because the influence of global warming is largely offset by the impact on the mode of stratospheric mid‐ and high‐latitude ozone increases caused by greenhouse gas increases, causing a weakening. Models simulating ozone as part of chemistry schemes on average show a larger influence on the mode due to ozone loss and a smaller influence of greenhouse gases than models that prescribe ozone. The results suggest that only relying on such “no‐chemistry” models for the attribution of trends in the mode can lead to incorrect results. Key Points The influences of ozone changes and greenhouses gases on the Southern Annular Mode are analyzed in CMIP6 simulations Ozone depletion exerts a stronger and GHGs a weaker influence on the Southern Annular Mode (SAM) in chemistry versus no‐chemistry models Three sensitivity experiments are explained considering an impact of GHGs onto the SAM resulting from ozone changes